Design of a compact biconical antenna for UWB applications - Rapin Kudpik (2018)
This paper presents the study, design, fabrication, and measurement of a vertically polarized compact biconical antenna that can be used as a reference antenna. The study from simulation results suggest that the optimal antenna shall have the flare angle of 60 which gave the most stable vertical beamwidth in the broadside direction and the fewest ripples in the main beam region, a cone length of one wavelength of center frequency (7 GHz) to make the antenna most compact, and the feed gap was 0.5 mm. The return loss was 10 dB on average across the bandwidth. The simulation results were validated by the experiments. The fabricated antennas worked across 2-12 GHz as desired, and were used as reference antennas especially for UWB 3.1-10.6 GHz applications. © 2011 IEEE.